PERANCANGAN SISTEM PERIZINAN DAN MONITORING SISWA KELUAR KAWASAN SEKOLAH BERBASIS WEBSITE DENGAN METODE SCRUM (STUDI KASUS : SMA DARUL MA’ARIF JAKARTA SELATAN) - Mohamad Adnan Kasogi; Mochamad Adhari Adiguna (PT Triputra Sejahtera Prima, 2025)
The management of student permits to leave the school area is an essential aspect of maintaining security, discipline, and the school’s responsibility toward students. The manual system currently used still has several weaknesses, including delayed validation, susceptibility to data manipulation, limited access to information, and difficulties in monitoring by teachers and parents. This study aims to design a web-based student permit and monitoring system with a case study at SMA Darul Ma’arif, South Jakarta. The research method was conducted through observation, interviews, literature study, and documentation to identify problems in the existing system. The software development process applied the Scrum method, which is iterative and adaptive, consisting of stages such as product backlog, sprint planning, sprint, daily scrum, sprint review, and sprint retrospective. The proposed system provides features for digital permit applications, validation by teachers on duty and security staff, automatic recording of student check-in and check-out, and integrated notifications for parents. The research results show that the developed system improves the effectiveness of permit recording, accelerates reporting, reduces the potential for permit misuse, and provides data transparency for both the school and parents. With this system, student monitoring outside the school area becomes more efficient, accurate, and structured, thereby supporting the creation of a safe, orderly, and trustworthy school environment.